THE ROLE OF BANKS IN THE DEVELOPMENT OF FINANCIAL RELATIONS OF REGIONS (Conferencea, 2023)
This article explores the multifaceted role of banks in shaping the financial landscape of regions and their development. It discusses how banks serve as intermediaries, promoters of economic growth, enablers of financial inclusion, and contributors to infrastructure investment. The article emphasizes the significance of banks in fostering balanced regional development, facilitating efficient resource allocation, and promoting financial stability. By analyzing the various functions of banks within the context of regional financial relations, this article highlights their essential contributions to the i